A Review of Key Factors That Affect University Building Maintenance Costs - Palis, Prescilla; Saidin Misnan, Mohd (International Journal of Engineering and Technology, 2018)
As Malaysia continues to focus its efforts on becoming an education hub, universities are vital places where learning processes, teaching and research activities are conducted. A university is a factor of production in producing graduates, and the university buildings are considered to be assets and resources. Hence, to prolong a university building lifecycle to ensure all university activities continue performing at an optimum level, building maintenance management is vital. Despite the fact that several previous studies have been conducted in this area, there continues to be maintenance issues surrounding university buildings. The maintenance of university buildings has always been viewed as an insignificant activity. Therefore, the objective of this paper was to critically review key factors that affected maintenance costs of university buildings, and consequently propose different approaches to resolve this issue. The present paper reviewed related literature from previous studies and publications. As a result of the comprehensive review, it was identified that key factors that affected university building maintenance costs were fund allocations allocated by university management teams for maintenance departments, user behaviours, environmental factors, university design complexities and the quality of components and materials of university buildings. Each factor identified was critically examined and addressed to ensure that university buildings would be well-maintained.Â Â